Comment on: `Reliability of a commercially available and algorithm-based kinetic analysis software compared to manual-based software - dos Santos, T.; Lake, J.; Comfort, P. (Sports Biomechanics, 2022)
We read with interest the published study regarding the reliability and comparison between manual- and algorithm-based kinetic analysis software by Carroll et al. (2019) entitled: `Reliability of a commercially available and algorithm-based kinetic analysis software compared to manual-based software` DOI: 10.1080/14763141.2017.1372514 (SPONET-ID: 4053329), and we congratulate the authors for producing an informative and interesting study. However, we would like to raise an issue regarding the interpretation of their results for the differences in peak force (PF) between the two methods. We outline this issue in further detail in the following paragraphs of this letter.